Day-ahead economic dispatch of microgrid based on game theory - Sun, Lu; Xu, Qingshan; Chen, Xi; Fan, Yukai (Energy reports, 2020)
Utility and users are two important subjects in power dispatching, and each participant wants to maximize its benefits. That is to say, utility and users are engaged in an interest game with each other. In this paper, a day-ahead economic dispatch strategy which can solve mixed integer programming problem based on game theory is proposed. First, build the model of the microgrid. Second, set optimization objectives of utility and users and analyze constraints. Last, propose a dispatch strategy to ensure that utility and users gain the maximum benefits. A case study verifies the effectiveness of the proposed approach.